The Mineral Industry Of Alabama - Ronald B. Hollenbeck (The National Institute for Occupational Safety and Health (NIOSH), 1970)
The value of mineral production in Alabama continued to increase and reached a new high of $260 million, 3 percent above the previous high established in 1967. Record high values were reported for bentonite, crushed marble, lime, miscellaneous clay, portland cement, salt, sand and gravel, and scrap mica. The value of coal, total cement, petroleum, and stone accounted for 87 percent of the State's total value of mineral production. Alabama ranked second among the States in the production of bauxite and scrap mica and third in kaolin, masonry cement, and native asphalt.